Grain size controls on long-chain diol distributions and proxy signals in marine sediments - Lattaud, Julie; Eglinton, Timothy Ian; Tallon, Marie; Bröder, Lisa; Erdem, Zeynep; Ausín, Blanca (Frontiers in Marine Science, 2022)
Long chain alkyl diols (LCDs) are lipid biomarkers that occur ubiquitously in sediments. Their abundance and distributions are increasingly used as the basis of molecular proxies for environmental parameters such as sea surface temperature (SST) via the Long chain Diol Index (LDI), and upwelling intensity and nutrient conditions (parametrized as diol indices, DI-2, and Nutrient Diol Index, NDI, respectively). Their marine producers remain the subject of debate, but in cultures, they can be found within the outer wall (algaenan) of eustigmatophytes or in Proboscia diatoms. LCDs appear to be well preserved in sediments, potentially as a result of their association with algaenan and/or minerals, but little is known of their pre-depositional histories, in particular transport dynamics. Here, 15 surface continental margin sediments as well as one high-deposition-rate sediment core (50 cm, spanning the last ~30 years) were analyzed in order to evaluate the impact of organo-mineral associations, lateral transport, and hydrodynamic sorting on sedimentary LCD signals. The abundance and distribution of LCDs in bulk sediments and corresponding grain-size fractions was determined. The highest proportion of all LCD isomers is found in the fine fraction (2 – 10 µm), which also holds the highest proportion of organic matter in relation to the other grain-size fractions. However, LCDs are also found in the other fractions (sand, coarse silt, and clay), and their concentrations are not correlated with bulk organic carbon content, indicating different preservation or transport mechanisms. LDI-SST in the bulk sediment is comparable to the mean annual SST at all sites except those influenced by upwelling and characterized by strong seasonal SST gradients. To the contrary of other biomarker-related proxies (e.g., alkenones), lateral transport does not appear to strongly affect LDI-SST in size fractions, suggesting that the intimate relationship of LCD with the algaenan may counteract the influence of hydrodynamic mineral sorting processes on related proxy signals. The difference between the fraction-weighted LCD concentration and bulk sedimentary LCD concentration indicates potential release of LCD during laboratory fractionation, suggesting degradation of algaenan or dissolution of opal frustules.